Meningkatkkan Kemampuan Literasi Numerasi Dengan Model Problem Based Learning (PBL) Ditinjau Dari Self Confidence Siswa SMK - Fachri Awami; Yuyu Yuhana; Hepsi Nindiasari (Universitas Mathla'ul Anwar Banten, 2022)
The purpose of this study was to determine the increase in student numeracy literacy taught using the Problem-Based Learning (PBL) Learning Model in terms of Self-Confidence. The low numeracy literacy ability of students so that it is necessary to apply a learning model that trains students' abilities as well as fosters student confidence. The method used in this study is a quasi-experimental method that uses a treatment by level 2x2 design design. The consideration of using this design is to see the answers to research questions from two different treatments, namely: the treatment of problem-based learning (PBL) models in the experimental class and conventional models in the control class. The results of the study revealed that the numeracy literacy skills of students who were taught using the PBL learning model were better than students who were taught using the conventional learning model, which had a significant difference; The numeracy literacy ability of students who have high self-confidence is higher than students who have low self-confidence. The results of the study reveal that (1) there are differences in numeracy literacy skills between students who study using the problem-based learning (PBL) learning model and students who study conventionally; (2) There are differences in numeracy literacy skills between students who have high self-confidence and students who have low self-confidence; (3) There is no interaction effect between the application of learning models and self-confidence on students' numeracy literacy abilities; (4) There are differences in numeracy literacy skills between students who learn to use the problem based learning (PBL) learning model and high self-confidence and students who learn to use conventional and high self-confidence; (5) There are differences in numeracy literacy skills between students who learn to use problem based learning (PBL) and low self-confidence and students who learn to use conventional and low self-confidence;Keywords : Literacy Numercy, PBL, Self Confidence